Oral Presentations Abstracts: COMMERCIAL MHEALTH APPS AND EXPLOITATIVE VALUE TRADE-OFFS - ROSSMAIER, Leon (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Mobile health (mHealth) apps are becoming progressively important for primary care, disease prevention, and public health interventions. They promise to empower its users by offering them more independence, better access to health services, and more insight into their health status resulting in better informed medical decision-making and lifestyle changes. Disadvantages of mHealth apps often include a lack of privacy protection, a decrease in personal attachment, and the acceptance of a normative conception of health challenging the user’s self-determination. Privacy, attachment, and self-determination are, alongside health, linked to fundamental dimensions of human well-being. Users of mHealth apps can either accept those disadvantages or abstain from using this technology entirely. Users, therefore, have to trade-off fundamental dimensions of well-being to gain a certain health benefit if they want to use commercial mHealth apps. This presentation will clarify the values most relevant in this context, focusing on privacy, self-determination, and attachment. I claim that these values imply fundamental conditions of well-being that should not be undermined, especially in the context of health care. I will argue that the value trade-offs users must engage in are an instance of mutually advantageous agreements by which the provider of the app takes unfair advantage of the user. This renders such agreements exploitative. I will discuss the notion of exploitation that I think applies in this case and explain under what circumstances exploitative agreements that come with the use of commercial mHealth apps oppose the empowerment narrative.